Da cozinha ao terreiro em Mutamba da Caieira (RN) : cotidiano, espaço doméstico e sociabilidade - Silva, Marilu Albano da (2008)
In this work we thought about the social use of the domestic space and, specifically, the space destined to the preparation of food. The kitchen is a creative space of social relationships. There the families exchange daily interaction with the neighbors, in a collective of the space reserved to the making of food. Our empiric research was in the Mutamba da Caieira community, located in the county of Assu (RN). The data was collected through the etnographic method aided by the photographic resources. In the discussion, we delimitated at the house three types of kitchens: one reserved to the family, another kitchen in the terrace and yet another kitchen in the yard. They are kitchens that link amongst themselves with activities and differentiated temporalities. In the daily social exchange, the kitchen imposes itself as a social space through the conditions that it offers for the production of the foods, the circulation of domestic objects, the communication of knowledge around the cookery, operating a group of symbolic and ritual actions combined with appropriate techniques for the transformation of the foods. The study reveals that the domestic chores accomplished amon relatives and friends form webs of intracommunitary relationships in the use of the three kitchens, and that the social network is updated in a singular moment that usually happens in the community, the Game of Pacará